Soil organic matter status and penetration resistance at alley cropping system on degraded acid dryland - R D Yustika; M Muchtar (Brawijaya University, 2016)
Soil has important functions, one of which acts as a growing medium for plants so the soil environment should be able to support the growth and development of the plants in taking water and nutrient needs. The purpose of this study was to elucidate the effect of alley cropping on improvement of soil organic C status, and its impact on soil penetration. Observations of soil organic C status were done in 2008, 2011, and 2014, while observations of soil bulk density, C/N ratio, and penetration were conducted in 2014. Soil penetration was measured using penetrologger. Alley cropping systems applied were Flemingia congesta, Leucaena glauca, and Gliricida sepium. The results showed that the presence of hedgerow trees in alley cropping systems could supply organic materials periodically and could increase the content of organic C. The results of measurements of soil penetration in the surface layer (0-5 cm) showed low penetration values. The penetration value increased with increasing soil depth with the highest penetration value was at the depth of 15 cm.